DETERMINANTS OF THE INTENTION OF MUZAKKI TO PAY PROFESSIONAL ZAKAT - Hasan Mukhibad; Fachrurrozie Fachrurrozie; Ahmad Nurkhin (Faculty of Islamic Economics and Business, Universitas Islam Negeri Ar-Raniry, 2019)
The objective of this study is to empirically explore the effect of reputation, transparency, accountability of LAZ (Lembaga Amil Zakat or institutions that collect zakat which is a kind of Islamic tithe or alms), the religiosity of muzakki (communities who are obliged to pay zakat), and the trust of muzakki in LAZ on the strength of the intention of muzakki to pay professional zakat through amil (collectors). In addition, this study also attempts to empirically investigate the factors influencing the reputation of LAZ and the trust of muzakki in LAZ. The population of this study is civil servants in Pati District, Central Java, who already have an obligation to pay zakat. The sample of this study is determined by the incidental method and has produced 73 respondents. Data analysis uses the Structural Equation Model with the WarpPLS tool. Research showed empirically that the reputation of LAZ is positively influenced by the transparency and accountability of LAZ. The trust of muzakki in LAZ is influenced by the reputation of LAZ and the religiosity of muzakki. Furthermore, the strength of the intention of muzakki to pay zakat is influenced by the reputation of LAZ, the transparency of LAZ, the religiosity of muzakki, and the trust of muzakki in LAZ. The potential of zakat can be increased by improving LAZ performance (reputation, transparency) and the religiosity of muzakki.==============================================================================================Determinan Intensi Muzakki dalam Membayar Zakat Penghasilan. Penelitian ini secara empiris bertujuan untuk mengeksplorasi pengaruh reputasi, transparansi, akuntabilitas Lembaga Amil Zakat (LAZ), religiusitas muzakki, dan kepercayaan muzakki pada LAZ terhadap besaran keinginan muzakki untuk membayar zakat penghasilan melalui LAZ. Selain itu, penelitian ini juga bermaksud untuk secara empiris melakukan investigasi terhadap faktor-faktor yang mempengaruhi reputasi LAZ dan kepercayaan muzakki terhadap LAZ. Yang menjadi populasi dalam penelitian ini adalah para pegawai negeri sipil di Kabupaten Pati, Jawa Tengah, yang sudah sampai nishab zakat. Sampel untuk penelitian berjumlah 73 orang yang ditentukan dengan metode insidental sampling. Data lapangan kemudian dianalisis dengan Structural Equation Model dengan WarpPLS tool. Hasil kajian menunjukkan bahwa secara empiris reputasi LAZ secara positif dipengaruhi oleh transparansi dan akuntabilitas LAZ itu sendiri. Sedangkan kepercayaan muzakki terhadap LAZ dipengaruhi oleh reputasi LAZ dan religiusitas muzakki. Selanjutnya, besaran keinginan muzakki untuk membayar zakat dipengaruhi oleh reputasi, transparansi LAZ, religiusitas muzakki, dan kepercayaan muzakki terhadap LAZ. Potensi zakat bisa dimaksimalkan dengan meningkatkan kinerja LAZ (reputasi, transparansi), dan religiusitas muzakki.